The Use of Diorama Learning Media Towards Learning Motivation of Students in Class X IPS 2 - Imelda Setya Fitri; Zulfan Zulfan; Dara Rosita (Universitas Syiah Kuala, 2022)
The research entitled The Use of Diorama Learning Media on Student Motivation in Class X Social Sciences 2 SMA Negeri 1 Rundeng District